Sikap Dan Perilaku, Kinerja Produk, Kepuasan Dan Loyalitas Konsumen Kopi Bubuk (Studi Kasus Pada Usaha Kopi Bubuk Rantau Di Kecamatan Argamakmur Kabupaten Bengkulu Utara) - Sandy, M. Ilwanda; Utama, Satria Putra; Reswita, Reswita (Metta : Jurnal Ilmu Multidisiplin, 2021)
The purpose of this study was to analyze consumer attitudes and behavior, level of product importance and performance, satisfaction, and consumer loyalty to RANTAU ground coffee in Argamakmur District, North Bengkulu Regency, Bengkulu Province. The place where the research was carried out was in the RANTAU ground coffee business in ArgaMakmur District, North Bengkulu Regency, Bengkulu Province. In this study the data consists of secondary data and primary data. Primary data is taken by direct observation of the production process, interviews with customers of Rantau ground coffee, based on a list of questions or questionnaires that have been prepared. The secondary data in this study consisted of an overview of the RANTAU ground coffee business obtained directly from the RANTAU ground coffee business actor, books related to consumer behavior, satisfaction, and loyalty, previous research journals that have been published, both online and online. not online related to research. The research sample, namely consumers of RANTAU ground coffee, was taken by accidental sampling. The data analysis method used quantitative analysis method, Importance Performance Analysis (IPA) method, the Customer Satisfaction Index (CSI) method, and to analyze the level of consumer loyalty using the Loyalty Pyramid. The results of the study are consumer attitudes and behavior in making decisions to consume RANTAU ground coffee for reasons of good taste with an average frequency of consuming the product 3 times a day, the number of last purchases an average of 0.25 kilos. Consumers are satisfied with the product and intend to return to consume the product. If the product is not available at the location of purchase, consumers will go elsewhere to buy RANTAU ground coffee products. The measurement of product attribute performance with IPA from RANTAU coffee powder products, must be improved or improved, the attribute performance is the expiration date that has not been listed on the product. On average, consumers are satisfied with the RANTAU ground coffee business. Consumer satisfaction of RANTAU ground coffee is 66% which shows that consumers are satisfied overall. RANTAU ground coffee consumers are already in the loyal category because the value of consumers who are disloyal / like to switch coffee brands or switcher buyers (34%) is smaller than the value of consumers who are loyal to buying Rantau ground coffee or Committed buyers (66%).